Interação estrela planeta: sobre o magnetismo de planetas gigantes gasosos - Nascimento, Sanzia Alves do (2012)
In this thesis we analyze the effects that the presence of a near gas giant planet can cause in its host star. It has been argued that the star planet interaction can cause changes in the coronal and chromospheric stellar activity. With this in mind, we analyze a sample of 53 extrasolar planets orbiting F, G and K main sequence stars, among them three super-Earths. In this analysis, we look for evidence of changes in the chromospheric activity due to the proximity of the giant planet. We show that, so far, there is not enough evidence to support such a hypothesis. Making use of the same sample and also taking in account available data for the Solar System, we revisit the so-called magnetic Bode s law. This law proposes the existence of a direct relationship between magnetism and rotation. By using estimations for the stellar and planetary magnetic momentM and the angular momentumL, we construct a Blackett s diagram (logL 􀀀logM). In this diagram is evident that the magnetic Bode s law is valid for both the Solar System and the new planetary systems